Gap between words and action: empirical study on the consistency of farmers supporting green vegetable production practices - Li, Bo; Liao, Mengjie; Yuan, Junjing (Frontiers in Sustainable Food Systems, 2023)
The increasing interest on the quality and safety of vegetables has focused much attention to the words (willingness) and action (behavior) of farmers toward the production of safe vegetables. However, the majority of studies typically focus on willingness or behavior, ignoring the interactions between the two. Moreover, there exists a wide gap between farmers’ actual behavior and their willingness to support green production practices of vegetable. Thus, in order to explore the key factors of farmers’ willingness, behavior, and their consistency to adopt green vegetable production vegetable practices, we performed bivariate probit modeling and binary logistic regression based on a survey of 452 farmers in Beijing, China. Results demonstrate the number of farmers willing to adopt green vegetable production practices to exceed those who do not by 65.5%. In particular, 73.9% of farmers adopt green vegetable production practices, while 67.5% of farmers exhibit an adoption willingness that is consistent with the adoption behavior. A positive correlation is observed between the willingness and behavior to adopt green production practices of vegetable, while the key influencing factors of the willingness, behavior, and consistency of green production practices are distinct. For example, cooperatives, neighboring farmers, and government regulation exert a significant positive impact on consistency, while family labor force, vegetable income, and the media have a significant negative impact. Moreover, cooperatives are identified as the most important influencing factor. Our work offers guidance in understanding the influencing factors of the willingness and behavior to adopt green vegetable production practices, and can provide a policy basis for governments to promote such practices.